Anosognosia in Alzheimer disease: Disconnection between memory and self‐related brain networks. Issue 3 (21st July 2015) - Perrotin, Audrey; Desgranges, Béatrice; Landeau, Brigitte; Mézenge, Florence; La Joie, Renaud; Egret, Stéphanie; Pélerin, Alice; de la Sayette, Vincent; Eustache, Francis; Chételat, Gaël
<x xml:space="preserve">Abstract</x> Objective Impaired awareness is a common symptom in many mental disorders including Alzheimer disease (AD). This study aims at improving our understanding of the neural mechanisms underlying anosognosia of memory deficits in AD by combining measures of regional brain metabolism (resting state fluorodeoxyglucose positron emission tomography [FDG‐PET]) and intrinsic connectivity (resting state functional magnetic resonance imaging [fMRI]). Methods Twenty‐three patients diagnosed with probable AD based on clinical and biomarker data and 30 matched healthy control subjects were recruited in this study. An anosognosia index (difference between subjective and objective memory scores) was obtained in each participant. Resting state FDG‐PET for glucose metabolism measurement and resting state fMRI for intrinsic connectivity measurement were also performed. AD and control groups were compared on behavioral data, and voxelwise correlations between anosognosia and neuroimaging data were conducted within the AD group. Results AD patients underestimated their memory deficits. Anosognosia in AD patients correlated with hypometabolism in orbitofrontal (OFC) and posterior cingulate (PCC) cortices. Using OFC and PCC as seed regions, intrinsic connectivity analyses in AD revealed a significant association between anosognosia and reduced intrinsic connectivity between these regions as well as with the medial temporal lobe. Interpretation Anosognosia in AD is due not only to functional changes within cortical midline structures involved in self‐referential processes (OFC, PCC), but also to disconnection between these regions as well as with the medial temporal lobe. These findings suggest that the lack of awareness of memory deficits in AD results from a disruption of the communication within, but also between, the self‐related and the memory‐related brain networks. Ann Neurol 2015 Ann Neurol 2015;78:477–486